Sentimentos de profissionais de enfermagem diante da morte de recém-nascidos em uma unidade de terapia intensiva - Silva, Laureana Cartaxo Salgado Pereira da (2006)
To understand the feelings of nursing professionals when faced with the death of newborn babies in an intensive care unit is the purpose of this investigation. Motivation was triggered by the countless hardships we go through everyday, as professionals, and the scarcity of publications in this specific area of knowledge. The aim is to describe the experience of the nursing professionals and identify their feelings when faced with the death of newborn babies in an intensive care unit. As a methodological procedure, this research is based on a qualitative, phenomenology-focused approach and on the following leading question addressed to the interviewed nurses and nursing technicians who work at the unit: How do you feel when you are faced with the death of a newborn baby in the ICU at which you work? Answers to this question on such phenomenon revealed a diversity of feelings, such as, loss, guilt, failure, negation, compassion, and sorrow, coupled with anguish, fear, and anxiety, resulting in an experience of the sensitive world of everyone. Theoretical support to this analysis was based on works by authors who discuss phenomenology, as well as authors who study the theme of death. An understanding of the phenomenon thus studied enables us to affirm that the death of a newborn baby is, for the nursing professional who takes care of the baby in the space of the ICU, an experience of conflicting, sometimes painful feelings, on account of their complexity. This is true not only in respect of their feelings for the baby, but for the family as well, especially the parents